Kajian Model Estimasi Erosi Tanah Menggunakan Pendekatan Modified Universal Soil Loss Equation (MUSLE) Studi Kasus Hulu Kanal Duri - Andreas Panjaitan; Imam Suprayogi; Trimaijon Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Sedimentation-erosion that happed at top canal of Duri is one of problem that must be described in analyzing DAS because canal of Duri is multifunction of canal that usefull in wealth of people. Method that used is analysis using some formulas of erosion-sedimentation such as USLE and MUSLE, MUSLE it self is the development of USLE method by changing erosivitas factor with flow factor. Prediction result of erosion potential with MUSLE model show that sedimentation happened at top canal of Duri condition of closing land 2012. It has amount 31.16 ton and in 2002 was 29.38 ton. It shows that sedimentation that happened 2012 was bigger than the sedimentation that happened before in 2002. This happened, because of the changing of closing land happened, had caused the increase of top debit in rain. as a result of the increasing of koefisien of surface flow. Erosion prediction with USLE model at top canal of Duri in 2002 was 45.72 ton/ha/year. Show that the result depends on how high the rain falls. The higher of rain falls the bigger of land erosion. Key word: Erosion-sedimentation, closing land, rain falls